Progress in the Understanding of the Mechanism of Tamoxifen Resistance in Breast Cancer - Yao, Jingwei; Deng, Kun; Huang, Jialu; Zeng, Ruimin; Zuo, Jianhong (Frontiers in Pharmacology, 2020)
Tamoxifen is a drug commonly used in the treatment of breast cancer, especially for postmenopausal patients. However, its efficacy is limited by the development of drug resistance. Downregulation of estrogen receptor alpha (ERα) is an important mechanism of tamoxifen resistance. In recent years, with progress in research into the protective autophagy of drug-resistant cells and cell cycle regulators, major breakthroughs have been made in research on tamoxifen resistance. For a better understanding of the mechanism of tamoxifen resistance, protective autophagy, cell cycle regulator, and some transcription factors and enzymes regulating the expression of the estrogen receptor have been summarized in this review. In addition, recent progress in reducing resistance to tamoxifen was reviewed. Finally, we discussed the possible research directions into tamoxifen resistance in the future to provide assistance for the clinical treatment of breast cancer.